Correctional Medical Care for Female Prisoners: Legal Issues Surrounding Inadequate Treatment of Chronic and/or Preexisting Health Conditions - Lamberton, Chelsi (The prison journal, 2022)
Research shows incarcerated women suffer more chronic and/or preexisting health conditions than their male counterparts. Through the lens of federal court litigation pursuant to Title 42 U.S. Code Section 1983, this article discusses women who brought legal challenges, questioning the adequacy of correctional medical care rendered to their chronic and preexisting health conditions. Case law reveals several trends, including multiple disease co-morbidities, malingering, medication administration, free-world specialty care, diagnostic and treatment limitations, and mental illness. The article concludes with policy implications, suggestions for future research, and recommendations for accelerated research on the chronic and/or preexisting health conditions of female prisoners.